ADT: The automatic weather station data tool - Faniriantsoa, Rija; Dinku, Tufa (Frontiers in Climate, 2022)
Climate data are essential in an array of climate research and applications. Climate data also provide the foundation for the provision of climate services. However, in many parts of Africa, weather stations are sparse and their numbers have been declining over the last half-century. The distributions of existing meteorological stations are also uneven, with most weather stations located in towns and cities along the main roads. There have been some efforts over the last decade to expand the meteorological observation network in many parts of Africa. This is mainly driven by donor funding and is being accomplished through the installation of Automatic Weather Stations. Automatic Weather Stations offer a number of advantages over the conventional ones, which include automated reporting at a very fine temporal resolution (15 minutes on average). And the disadvantages include high maintenance needs that require spare parts that may not be available locally. The other challenge many National Meteorological Services are facing is that different donors provide different station types. The data collected by these different systems or networks are in different formats and may sit on different servers. Accessing, processing, and using these data has been a serious challenge. The Automatic Weather Station Data Tool (ADT) has been developed to address this particular challenge. This free web-based application, with an easy-to-use graphical user interface, enables National Meteorological Services to access, process, quality control, and visualize data from different Automatic Weather Station systems in one place. It also enables real-time monitoring of stations to see which ones are working and which ones are offline. National Meteorological Services could also use ADT for sharing observations with the public on a real-time basis. ADT has been implemented in five countries in Africa (Ethiopia, Ghana, Kenya, Rwanda, and Zambia), and there is already a very high demand for it.